Digital Literacies Go to School: A Cross-Case Analysis of the Literacy Practices Used in a Classroom-Based Social Network Site. Issue 2 (2nd April 2016) - Lindstrom, Denise L.; Niederhauser, Dale S.
ABSTRACT: The authors, working from a new literacies studies perspective, suggest that educators can better teach their students if they develop their own knowledge of the purposes, types, and language conventions students use in their informal out-of-school literacy practices. The purpose of this study was to identify the literacy practices used in a classroom-based social network site and determine how these practices reflect digital literacies. By connecting differences in the literacy practices of three fifth-grade girls to the instructional moves made by classroom teachers, the authors were able to identify and describe how classroom teachers unintentionally marginalized the kinds of digital literacies that are valued in the larger society. Findings point to the importance of creating online identities for establishing relationships in a social networking site and a need for teachers to model ways to shift language use when engaging in different writing contexts.